Peran Ekstrakulikuler Seni Teater dalam Meningkatkan Rasa Percaya Diri Siswa SDN 1 Bung Kandong - Iga Danuarta; Juliadi; Jumatriadi (Al-Faiza : Journal of Islamic Education Studies, 2024)
High-quality human resources is an absolute requirement for achieving successful national development. This can only be obtained through education which is a vehicle for improving higher quality Human Resources (HR). This research was conducted with the following objectives: 1) to describe how to increase the self-confidence of students at SDN 1 Embung Kandong; 2) to know what the extracurricular role of the theater arts is in increasing the self-confidence of students at SDN 1 Embung Kandong; 3) to find out the difference in self-confidence of students at SDN 1 Embung Kandong who attended and those who did not take part in extracurricular theater arts. This study uses a qualitative method. The population of this study was SDN 1 Embung Kandong, the samples used as data sources were students at SDN 1 Embung Kandong who attended art galleries, teachers, and mentors. The process of collecting data using observation, interviews, and documentation. Based on this description, the results of the study show that: The coaching process to increase the self-confidence of students at SDN 1 Embung Kandong is carried out through extracurricular activities in theater arts. Theater arts extracurriculars have a very significant role in increasing the confidence of students at SDN 1 Embung Kandong. Students who take part in extracurricular theater arts have higher self-confidence.